Contrabandos e descaminhos nas fronteiras de Mato Grosso : um olhar da imprensa (1952 – 1979) - Mota, José Cicero da (2014)
This dissertation is a study of the history of contraband and embezzlement of Mato Grosso border with Bolivia and Paraguay in the period between the years 1952 and 1979, and attempting some historical dimensions of the forms of representation of the unlawful practice produced discourses present in the press - articles, advertisements, news. Although the analysis on contraband and embezzlement is the dominant theme, the research seeks to understand the formation of the border itself the object of study for this, despite the chronological cut to be between the years 1952-1979, it was necessary to go back to the previous period the discovery and occupation of Mato Grosso in order to understand how was the training border between the three countries, as well as the dynamics of the practice of smuggling. The smuggling and contraband seems to have been established for a long time the basis of economic relations that have developed in this border region, however, this practice transcends the purely economic level, setting up a major part of all the social relations that have occurred throughout history between border populations.